Urea Is Both a Carbon and Nitrogen Source for Microcystis aeruginosa: Tracking 13C Incorporation at Bloom pH Conditions - Krausfeldt, Lauren E.; Farmer, Abigail T.; Castro Gonzalez, Hector F.; Zepernick, Brittany N.; Campagna, Shawn R.; Wilhelm, Steven W. (Frontiers in Microbiology, 2019)
The use of urea as a nitrogenous (N) fertilizer has increased over the past two decades, with urea itself being readily detected at high concentrations in many lakes. Urea has been linked to cyanobacterial blooms as it is a readily assimilated N-source for cyanobacteria that possess the enzyme urease. We tested the hypothesis that urea may also act as a carbon (C) source to supplemental growth requirements during the alkaline conditions created by dense cyanobacterial blooms, when concentrations of dissolved CO2 are vanishingly low. High rates of photosynthesis markedly reduce dissolved CO2 concentrations and drive up pH. This was observed in Lake Erie during the largest bloom on record (2015) over long periods (months) and short periods (days) of time, suggesting blooms experience periods of C limitation on a seasonal and daily basis. We used 13C-urea to demonstrate that axenic cultures of the model toxic cyanobacterium, Microcystis aeruginosa NIES843, assimilated C at varying environmentally relevant pH conditions directly into a spectrum of metabolic pools during urea hydrolysis. Primarily, 13C from urea was assimilated into central carbon metabolism and amino acid biosynthesis pathways, including those important for the production of the hepatotoxin, microcystin, and incorporation into these pathways was at a higher percent during growth at higher pH. This corresponded to increased growth rates on urea as the sole N source with increasing pH. We propose this ability to incorporate C from urea represents yet another competitive advantage for this cyanobacterium during dense algal blooms.